2015
DOI: 10.14712/18059694.2015.93
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Brief Bedside Dysphagia Screening Test – Revised: a Cross-Sectional Czech Study

Abstract: Summary:Aim: The purpose of this study was to develop a revised version of the Brief Bedside Dysphagia Screening Test for determining penetration/aspiration risk in patients prone to dysphagia. The priority was to achieve high sensitivity and negative predictive value. Methods: The study screeners conducted bedside assessment of the swallowing function in 157 patients with a neurological (mainly stroke) or an ear, nose, and throat diagnosis (mainly head and neck cancer). The results were compared with a gold s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 26 publications
2
30
0
6
Order By: Relevance
“…5 Assessment of the patient's ability to swallow liquids and solids of varying consistencies can yield important information to corroborate, or contradict, self-report of dysphagia symptom location and severity, which can be inaccurate. 6,7 Although assessments of swallowing abilities exist, [8][9][10][11][12][13][14] rapid methods are limited to oropharyngeal dysphagia in non-GI patient populations. A review of these tools found most lack consistent sensitivity to identify dysphagia and are limited in generalizability due to homogeneous samples.…”
Section: Introductionmentioning
confidence: 99%
“…5 Assessment of the patient's ability to swallow liquids and solids of varying consistencies can yield important information to corroborate, or contradict, self-report of dysphagia symptom location and severity, which can be inaccurate. 6,7 Although assessments of swallowing abilities exist, [8][9][10][11][12][13][14] rapid methods are limited to oropharyngeal dysphagia in non-GI patient populations. A review of these tools found most lack consistent sensitivity to identify dysphagia and are limited in generalizability due to homogeneous samples.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important decision points involves determining whether patients with stroke appear to be suffering from swallowing difficulties; to this end, various bedside screening tests have been developed (O'Horo et al, 2015). The Brief Bedside Dysphagia Screening Test-Revised (BBDST-R) is a simple 8item dysphagia screening tool with high sensitivity (95.5%; 95% confidence interval CI [CI] = 84.9-98.7%) and negative predictive value (88.9%; 95% CI = 67.2-96.9%) that is recommended for patients with neurological conditions (Mandysova et al, 2015). Both the preliminary version of the tool, the Brief Bedside Dysphagia Screening Test (BBDST) (Mandysova et al, 2011), and the BBDST-R (Mandysova et al, 2015) were developed in the Czech Republic based on a comparison of a simple bedside assessment and a quick swallow test with the gold standard, flexible endoscopic examination of swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…The Brief Bedside Dysphagia Screening Test-Revised (BBDST-R) is a simple 8item dysphagia screening tool with high sensitivity (95.5%; 95% confidence interval CI [CI] = 84.9-98.7%) and negative predictive value (88.9%; 95% CI = 67.2-96.9%) that is recommended for patients with neurological conditions (Mandysova et al, 2015). Both the preliminary version of the tool, the Brief Bedside Dysphagia Screening Test (BBDST) (Mandysova et al, 2011), and the BBDST-R (Mandysova et al, 2015) were developed in the Czech Republic based on a comparison of a simple bedside assessment and a quick swallow test with the gold standard, flexible endoscopic examination of swallowing. The largest subgroup was comprised of patients with stroke (54 of 112 patients or 48%) (Mandysova et al, 2015); therefore, the BBDST-R could be ideal for use in such patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations